A Comparative Immunohistochemical Expression of Cyclin D1 in Keratocystic Odontogenic Tumor, Dentigerous and Radicular Cysts - Yasamin H Al-Amiri; Lehadh M Al-Azzawi (College of Dentistry/ University of Baghdad, 2016)
Background: Odontogenic cysts include a group of osseodestructive lesions that frequently affect the jaws. Those cysts could derive from odontogenic epithelium and occur in the tooth-bearing regions of the jaws. The aims of this study were to evaluate the immunohistochemical expression of Cyclin D1 in Keratocystic Odontogenic Tumor, Dentigerous cyst and Radicular cyst in epithelium and connective tissue capsule. Materials and Methods: In this study, thirty formalin fixed paraffin embedded tissue blocks of Odontogenic cysts and Tumor, consist of 14 Keratocystic Odontogenic Tumor, 8 dentigerous cysts and 8 radicular cysts were analyzed immunohistochemically for the presence of Cyclin D1 proteins. Results: Strong to moderate expression of Cyclin D1 in epithelium was found in Keratocystic Odontogenic Tumor cases with positive cases percentage was (85.7%). Statistical significant differences (P